Guatemala City: a focus on working women and childcare (International Food Policy Research Institute, 2003)
The Hogares Comunitarios Program (HCP) was established in Guatemala City in 1991 as a direct response to the increased need for affordable and reliable childcare for women in urban Guatemala. The government-sponsored pilot program was designed as a strategy to alleviate poverty by providing working parents with low-cost, quality childcare within their communities. The program aimed at promoting child development and at filling the existing gap in preschool education in Guatemala. The pilot program rapidly expanded to both urban and rural areas of all 22 departments of the country. By 1998, the HCP comprised 1,200 hogares comunitarios (community daycare centers) that cared for approximately 10,000 children aged 0-7 years. In 2001, IFPRI performed an evaluation of this program's effectiveness.